AB0215 A LATE ONSET OF SYSTEMIC SCLEROSIS IS ASSOCIATED WITH A MORE RAPIDLY PROGRESSING CLINICAL PHENOTYPE IN LCSSC PATIENTS. (June 2019) - Moinzadeh, Pia; Kuhr, Kathrin; Müller-Ladner, Ulf; Siegert, Elise; Henes, Jörg; Riemekasten, Gabriela; Blank, Norbert; Schmalzing, Marc; Koetter, Ina; Guenther, Claudia; Schmeiser, Tim; Zeidler, Gabriele; et al.
Abstract : Background: SSc is a heterogeneous multisystem connective tissue disease. The majority of patients (pts) develop initial clinical symptoms between the ages of 30-50 years (yrs). It is not yet known whether the age of onset has an influence on the development of a distinct clinical phenotype. Objectives: Investigating the relationship between age at disease onset and the development of clinical characteristics using data of the German Network for Systemic Scleroderma. Methods: We evaluated 2928 patient data, subdivided them into 3 age groups at disease onset (<40 years, 40-60 years, and >60 years) and correlated the age at disease onset with specific clinical characteristics. Results: Overall, 24% of pts developed first non-RP symptoms at the age of <40yrs, 53% between the age of 40-60yrs, and 23% were older than 60yrs. In particular, SSc pts with disease onset >60yrs developed significantly (p<0.001) more often the lcSSc subtype (64%) as well as ACA antibodies (42%) with a significantly lower mRSS. They, however, also suffered more often from pulmonary hypertension (PH) and developed less often digital ulcers. Especially lcSSc pts were associated with a more rapidly progressing clinical phenotype, i.e., 25% of the elderly lcSSc pts developed PH after five years. In contrast, less than 5% diagnosed with lcSSc at the age of <40yrs suffered from PH after five yrs (p<0.001). Conclusion: In this registry, approximately one quarter of pts developed SSc at an age above 60yrs, predominantly having a lcSSc subtype. Although these pts have been diagnosed with the mild form of SSc, pts with a lcSSc subtype at a higher age (>60yrs) had more frequent a PH and showed a more rapid disease progression than the youngest pts. These findings may have an important influence on recommendations on diagnosis, frequency of follow-ups and therapy of SSc in different age groups. Disclosure of Interests: Pia Moinzadeh Speakers bureau: Actelion, Kathrin Kuhr: None declared, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Elise Siegert Shareholder of: Astra Zeneca, Grant/research support from: Actelion, Consultant for: AEC Partners, Speakers bureau: Actelion, Norsk, Jörg Henes: None declared, Gabriela Riemekasten Consultant for: Chugai, F. Hoffmann-La Roche, Speakers bureau: Chugai, F. Hoffmann-La Roche, Norbert Blank Grant/research support from: SOBI and Novartis, Speakers bureau: Novartis and SOBI, Marc Schmalzing Grant/research support from: Pfizer, Chugai, MSD, Janssen-Cilag, BMS, Celgene, UCB, Consultant for: Abbvie, Chugai, Genzyme, Hexal/Sandoz, MSD, Novartis, Roche, Sanofi Pasteur, Speakers bureau: Actelion, Baxalta/Shire, BMS, Celgene, Chugai, Janssen-Cilag, MSD, Novartis, Pfizer, Roche, UCB, Ina Koetter: None declared, Claudia Guenther Grant/research support from: Pfizer, Novartis, Employee of: 20 years ago, Novartis, Speakers bureau: Celtis, Tim Schmeiser Speakers bureau: Actelion, UCB, Pfizer, Gabriele Zeidler Grant/research support from: MSD Sharp & Dohme GmbH Actelion Pharmaceuticals Deutschland GmbH Roche Pharma AG AbbVie Deutschland GmbH Co. KG Pfizer Pharma GmbH Lilly Deutschland GmbH Celgene GmbH Bristol–Myers Squibb UCB Pharma GmbH/UCB GmbH Speakers bureau: MSD Sharp & Dohme GmbH Actelion Pharmaceuticals Deutschland GmbH Roche Pharma AG AbbVie Deutschland GmbH Co. KG Pfizer Pharma GmbH Lilly Deutschland GmbH Celgene GmbH Bristol–Myers Squibb UCB Pharma GmbH/UCB GmbH Disclosure of Interests: Alexander Kreuter Speakers bureau: Actelion Pharma, MSD, AbbVie, InfektioPharm, Margitta Worm: None declared, Laura Susok: None declared, Aaron Juche: None declared, Christiane Pfeiffer: None declared, Cord Sunderkoetter: None declared, Donja Homayoon: None declared, Nicolas Hunzelmann Speakers bureau: Boehringer Ingelheim, Actelion, Pfizer, Roche